Correlation of parity and age to services per conception, conception rate, and gestation length in Holstein Friesian cross cows - Ulfah, Norma Amalia; Samik, Abdul; Hariadi, Mas'ud; Suprayogi, Tri Wahyu; Hidanah, Sri (Ovozoa: Journal of Animal Reproduction, 2022)
Small farmers dominate dairy farming in Indonesia, and the average productivity is low. The contribution of domestic production only reaches about 23% of the total national milk consumption needs as a source of human nutrition. This study was aimed to identify the relationship between cow's parity and  age to services per conception (S/C), conception rate (CR), and gestation length (GL) of Holstein Friesian (HF) cross dairy cows. Data of this study consisted of primary data obtained from farmers interview, and secondary data from the Cooperative Unit of Argopuro village, Krucil, Probolinggo. Sample size was 200 cows, which was 10% of the total population. Data were analyzed for correlation and linear regression using the Statistic Package and Service Solution (SPSS) software version 20 (IBM Corp., USA) at a 95% confidence level. The average S/C, CR, and GL were 2.55 ± 1.57, 21%, and 278.19 ± 11.92 days, respectively. There was no significant correlation (p >0.05) between the parity with S/C, CR, and GL and the age with CR and GL. The only significant correlation (p <0.05) was between the age and S/C. Regression of S/C based on age followed the equation S/C = 0.104 + 0.407*age, with a correlation coefficient and determination coefficient of 0.733 and 0.538, respectively. It could be concluded that S/C could be predicted based on the age of the cows.